Investment facilitation for sustainable development: Getting it right for developing countries - Howard Mann; Martin Dietrich Brauch (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
The push for WTO negotiations leading to binding rules on investment facilitation is taking place without empirical analysis and without attention to developing country needs in facilitating investment for sustainable development. Investment-facilitation work belongs not in the WTO, but in organizations that focus on research, best practice and capacity building.
Keywords: 330